Analysis of the Impact of PT Waskita Karya Corruption on State Financial Accountability: Government Accounting Perspective - Muhammad Aras Prabowo; Siti Danila Hanipa; Fitriah Ulfah; Taufik Hidayadi; Mohammad Zuhdi; Nur Ain Ayunni Sabri (Mandalika Institute, 2025)
Corruption is one of the main problems facing developing countries, including Indonesia. Corruption cases involving State-Owned Enterprises (BUMN) such as PT Waskita Karya have a significant impact on state financial accountability. This research aims to analyze the impact of corruption at PT Waskita Karya on state financial accountability from a government accounting perspective. This research applies a descriptive approach through the literature study method. The research results show that corruption at PT Waskita Karya has a negative impact on state finances, reduces public trust, disrupts development projects, and damages the company's reputation. Government accounting has an important role in increasing transparency and accountability to prevent and overcome the impacts of corruption.